Interaction of BES1 and LBD37 transcription factors modulates brassinosteroid-regulated root forging response under low nitrogen in arabidopsis - Chai, Shuli; Chen, Junhua; Yue, Xiaolan; Li, Chenlin; Zhang, Qiang; de Dios, Víctor Resco; Yao, Yinan; Tan, Wenrong (Frontiers in Plant Science, 2022)
Brassinosteriods (BRs) play essential roles in plant growth, development and stress responses. BR signaling regulates multiple biological processes through controlling the activity of BES1/BZR1 family transcription factors. Besides the roles in promoting growth, BRs are also implicated in the root foraging response under low nitrogen conditions, however the mechanisms of the interaction of BR signaling and low nitrogen response remains unclear. Here we show that BES1 and LBD37 antagonistically regulate root foraging response under low nitrogen conditions. Both the transcriptional level and dephosphorylated level of BES1, is significant induced by low nitrogen, predominantly in root. Phenotypic analysis showed that BES1gain-of-function mutant or BES1 overexpression transgenic plants exhibits progressive outgrowth of lateral root in response to low nitrogen and negatively regulates repressors of nitrate signaling pathway and positively regulates several key genes required for NO3- uptake and signaling. In contrast, BES1 knock-down mutant BES1-RNAi showed significant reduction of their lateral root elongation response to low N. Furthermore, we identified a BES1 interacting protein, LBD37, which is a negative repressor of N availability signals. Our results showed that BES1 can interact with LBD37 protein and antagonize LBD37 transcriptional activity on N-responsive genes. Our results thus provide insight into the crosstalk of BR signaling and low nitrogen response.